Combined and single effects of elevated CO2 and temperatures on rice bakanae disease under controlled conditions in phytotrons. (8th February 2021) - Matić, Slavica; Garibaldi, Angelo; Gullino, Maria Lodovica
Abstract: Bakanae disease, caused by Fusarium fujikuroi, was investigated under different CO2 and temperature environments in order to simulate climate changes in the F . fujikuroi– rice pathosystem. F . fujikuroi ‐infected plants were grown under six phytotron conditions: low (18/22 °C night/day), medium (22/26 °C), and high (26/30 °C) temperature, at either ambient (450 ppm) or elevated (850 ppm) CO2 concentrations. Bakanae disease index (DI), seedling death incidence, fungal DNA quantity, and chlorophyll and carbohydrate contents varied significantly in infected plants as a consequence of changes in both CO2 and temperature. Plant height and dry weight were only influenced by single factors (temperature for height, and temperature or CO2 for dry weight), and not by the CO2  × temperature interaction. Medium and high temperatures (irrespective of the CO2 level) increased the DI significantly (range from 67.5% to 95.8%) compared to low temperatures (range from 45.8% to 47.5%). Under elevated CO2 levels, noticeable differences in the expression of four rice defence‐related genes and fungal DNA quantity were observed between those plants grown at higher temperatures and those at lower temperatures. Overall, combined and single effects of elevated CO2 and high temperatures seem to be favourable for bakanae disease development in the Mediterranean basin. Abstract : Combined and single effects of elevated CO2 and high temperatures were favourable for bakanae disease development in rice plants. Fungal quantity and plant death incidence varied significantly due to changes in CO2 and temperature.